Estrogen-dependent activation of TRX2 reverses oxidative stress and metabolic dysfunction associated with steatotic disease - Alfredo Smiriglia; Nicla Lorito; Marina Bacci; Angela Subbiani; Francesca Bonechi; Giuseppina Comito; Marta Anna Kowalik; Andrea Perra; Andrea Morandi (Cell Death and Disease)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) encompasses a spectrum of hepatic disorders, ranging from simple steatosis to steatohepatitis, with the most severe outcomes including cirrhosis, liver failure, and hepatocellular carcinoma. Notably, MASLD prevalence is lower in premenopausal women than in men, suggesting a potential protective role of estrogens in mitigating disease onset and progression. In this study, we utilized preclinical in vitro models—immortalized cell lines and hepatocyte-like cells derived from human embryonic stem cells—exposed to clinically relevant steatotic-inducing agents. These exposures led to lipid droplet (LD) accumulation, increased reactive oxygen species (ROS) levels, and mitochondrial dysfunction, along with decreased expression of markers associated with hepatocyte functionality and differentiation. Estrogen treatment in steatotic-induced liver cells resulted in reduced ROS levels and LD content while preserving mitochondrial integrity, mediated by the upregulation of mitochondrial thioredoxin 2 (TRX2), an antioxidant system regulated by the estrogen receptor. Furthermore, disruption of TRX2, either pharmacologically using auranofin or through genetic interference, was sufficient to counteract the protective effects of estrogens, highlighting a potential mechanism through which estrogens may prevent or slow MASLD progression.